Existentialism in the Development of Islamic Education Institutions: A Portrait of Excellent School Development of Yapita Primary School Surabaya - Mukaffa, Zumrotul (IAIN Samarinda, 2017)
This paper describes the development efforts of Islamic educational institution in order to maintain its existence in the midst of competition between educational institutions with various backgrounds of social religious organization communities that surround and underlie them. Yapita Primary School is a portrait of Islamic educational institution that is undergoing the process of development in the hope of becoming one of the best and excellent schools in Surabaya. It has undergone four (4) changes in its development process gradually, they are: First, the Traditional – isolative model that only held Islamic education. The second is the Synthesis model which is the implementation of Traditional-Isolative model with a little general education additions. Third, it brought a balanced education between Traditional – Isolative and general education model. Fourth, it integrates two Traditional-isolative models and Western-Modern model into a curriculum structure and enriched it with Student Talent-Interest Development and the excellent characteristics. Changes become necessity to be done so that its existence is still needed and sought by the community in the midst of the similar educational institutions emergence in the vicinity, among others; SD Luqman al-Hakim Hidayatullah Primary School, Muhammadiyah 26 Primary School, and al-Uswah Islamic Primary School.